2001
DOI: 10.1002/1529-0131(200106)44:6<1351::aid-art227>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled trial of methotrexate versus placebo in early diffuse scleroderma

Abstract: Objective Early diffuse scleroderma (systemic sclerosis; SSc) has no proven treatment. This study was undertaken to examine the efficacy of methotrexate (MTX) in improving the skin and other disease parameters in early diffuse SSc. Methods Seventy‐one patients with diffuse SSc of <3 years' duration were enrolled in a multicenter, randomized, placebo‐controlled, double‐blind trial. Thirty‐five patients were treated with MTX and 36 with placebo. Treatment was administered for 12 months. The primary outcome measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
163
0
14

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 362 publications
(178 citation statements)
references
References 12 publications
1
163
0
14
Order By: Relevance
“…In contrast trials of potential overall disease-modifying strategies in SSc have been disappointing. Immunomodulatory agents that have been evaluated include chlorambucil, methotrexate, and extracorporeal photopheresis (7)(8)(9). Putative antifibrotic or matrix-altering agents tested in SSc have included D-penicillamine, interferon-␣, ketanserin, and recombinant human relaxin (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…In contrast trials of potential overall disease-modifying strategies in SSc have been disappointing. Immunomodulatory agents that have been evaluated include chlorambucil, methotrexate, and extracorporeal photopheresis (7)(8)(9). Putative antifibrotic or matrix-altering agents tested in SSc have included D-penicillamine, interferon-␣, ketanserin, and recombinant human relaxin (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Despite these limitations, several studies have demonstrated that treatment with immunosuppressive agents, compared with placebo, resulted in statistically significant improvement in the MRSS in patients with early dcSSc (6)(7)(8). Thus, the skin score may be influenced by treatment, but the demonstration of this effect is likely to be hampered by spontaneous improvement.…”
mentioning
confidence: 99%
“…Raw data from a clinical trial in SSc suggested a beneficial treatment effect of methotrexate on skin score 5 . However, due to the small numbers of patients recruited into the trial and to limited power, the investigators had to correctly conclude that there was insufficient evidence to reject the null hypothesis of no treatment effect.…”
Section: Examplementioning
confidence: 99%